Short Notices (The ecumenical review, 1956)
Die Christliche Taufe als Rechtsakt nach dem Zeugnis der Frühen Christenheit, by Dr. Othmar Heggelbacher. Wegbereiter der Ökumene: Nathan Söderblom, John Mott, Marc Boegner, W. A. Visser't Hooft. Begegnungen und Erinnerungen von Hermann Maas, Hanns Lilje, Hans Stempel, Hans Hermann Walz. Les Protestants en Espagne, by Jacques Delpech. The Oppression of Protestants in Spain, by Jacques Delpech. Translation from the French by Tom and Dolores Johnson. Preface by Howard Schomer. Introduction by John A. Mackay. Die Evangelischen Christen Spaniens, Dokumente zu ihrer Lage, by Jacques Delpech. Geleitwort von Heinrich Bornkamm. The Old Testament and the Fine Arts, An Anthology of Pictures, Poetry, Music, and Stories Covering the Old Testament, by Cynthia Pearl Maus.